Increased levels of serum adenosine deaminase and increased risk of diabetic peripheral neuropathy in type 2 diabetes - Chao Yu; Lei Zhuang; Feng Xu; Li-hua Zhao; Xiao-hua Wang; Chun-hua Wang; Li-yan Ning; Xiu-lin Zhang; Dong-mei Zhang; Xue-qin Wang; Jian-bin Su (Frontiers in Endocrinology, 2022)
BackgroundIncreased serum adenosine deaminase (ADA) levels have been shown to be involved in metabolic abnormalities and immune disequilibrium, which may in turn contribute to inflammatory diseases. This study aimed to determine whether increased serum ADA levels are related to diabetic peripheral neuropathy (DPN) in patients with type 2 diabetes (T2D).MethodsThis study was part of a series exploring the potential risks for DPN. All patients received DPN assessment based on neuropathic symptoms, neuropathic signs, and nerve conduction studies to calculate the composite Z score of nerve latency, amplitude and conduction velocity (NCV). DPN was confirmed by both at least a presentation of neuropathic symptoms/signs and an abnormal nerve conduction index. Serum ADA levels were also synchronously detected.ResultsA total of 384 eligible patients with T2D were recruited for this study, and 24.5% (n=94) were determined to have DPN. Increases in serum ADA levels were closely associated with increases in composite Z score of latency (β=0.263, t=5.273, p<0.001) and decreases in composite Z score of amplitude (β=–0.126, t=–2.352, p=0.019) and NCV (β=–0.201, t=–3.841, p<0.001) after adjusting for other clinical covariates. Moreover, each 5 U/L increase in serum ADA levels was associated with a 1.781-fold increased adjusted odds ratio of having DPN (95% confidence interval: 1.271–2.495). Furthermore, the optimal cut-off value of serum ADA levels to discriminate DPN was ≥14.2 U/L (sensitivity=59.57%, specificity=75.52% and Youden index=0.351) after analysis by receiver operating characteristic curve.ConclusionsIncreased serum ADA levels may be a potential risk factor for DPN in patients with T2D.